Analisa Perbedaan Bahan Isolator (Glasswool, Tanah Liat dan Semen) Terhadap Efektifitas Proses Gasifikasi Batubara - Joko Rochmadi; Sudalto (G-Tech: Jurnal Teknologi Terapan, 2023)
Coal is one of the alternative energy sources in Indonesia as well as being the main fuel in several industries. The use of coal briquettes in Indonesia is a breakthrough in energy fulfillment. Coal gasification technology really needs to be developed in answering these problems. The purpose of research was to examine the coal gasification process, while the meaning of this study was to determine the best insulating material for the gasification process in terms of changes in temperature, time and air speed. Qualitative research methods (theory collection) and quantitative to achieve optimal results. This study used three different insulating materials including gaswool, clay and cement. The results of the analysis show that the clay insulator has the lowest temperature of 228 oC. The air velocity of the glasswool insulator is 2.56 m/s. The highest temperature comes from the cement insulator at 649 oC. Cement insulator, produces the best performance and efficiently expands from a burning time of 0 to 29 minutes, has an average air velocity of 9.20 m/s and an average temperature of 466.17 oC.